2006
DOI: 10.1016/j.commatsci.2005.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Studies on rate-dependent switching effects of piezoelectric materials using a finite element model

Abstract: The main goal of this paper consists in the modeling of rate-dependent behavior of piezoelectric materials within a three-dimensional finite element setting. We propose a rate-dependent polarization framework which is applied to cyclic electrical loading at various frequencies. The reduction in free energy of a grain is used as a criterion for the onset of the domain switching process. Nucleation in new grains and propagation of the domain walls during domain switching is modeled by a linear kinetics theory. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The main goal of the present study is the development of a three-dimensional coupled finite element model, extending previous elaborations by the authors reported in Arockiarajan et al (2005aArockiarajan et al ( , 2005b, to electromechanically induced rate-dependent domain switching of piezoelectric materials. The onset of domain switching is thereby initiated by means of an energy-based criterion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goal of the present study is the development of a three-dimensional coupled finite element model, extending previous elaborations by the authors reported in Arockiarajan et al (2005aArockiarajan et al ( , 2005b, to electromechanically induced rate-dependent domain switching of piezoelectric materials. The onset of domain switching is thereby initiated by means of an energy-based criterion.…”
Section: Introductionmentioning
confidence: 99%
“…In the progression of this work, a linear kinetics theory for the propagation of new phases through the material of interest is adopted; for a detail discussion the reader is referred to Delibas et al (2006) and Arockiarajan et al (2005a). In addition to the initiation of nucleation as based on Eq.…”
Section: Rate-dependencies Based On a Volume Fraction Conceptmentioning
confidence: 99%
“…Alternative modelling concepts, however, incorporated such interactions present in crystalline materials by means of the so-called Eshelby inclusion method in order to provide a mean field estimate of the effective response [15][16][17][18]. Intergranular effects are explicitly considered in several models in terms of related finite element formulations [19][20][21][22][23][24][25]. The local and average energy release during domain switching in ferroelectrics are rigorously derived in [26] with application to advanced polarisation switching models.…”
Section: Introductionmentioning
confidence: 99%
“…(17) is due to the term of Dd (I) kij r ij E k , hence in order to simplify the finite element calculation procedure, following Hwang et al [10], McMeeking and Landis [29], Kamlah [37] and Arockiarajan et al [57], the ferroelectric material is assumed to be isotropic elastic and isotropic dielectric, but the piezoelectricity coefficient d…”
Section: Principle Of Stationary Total Potential Energymentioning
confidence: 99%
“…Li and Fang [55] carried out 3D finite element simulations on ferroelectric materials. Kim and Jiang [56] and Arockiarajan et al [57] also developed a 3D finite element model for rate-dependent behavior of ferroelectric ceramics. ijk after the whole domain in the material element has switched.…”
Section: Introductionmentioning
confidence: 99%